Monosyllabic focus verbs disrupt reading fluency in Mandarin: evidence from eye-tracking - Zhang, Meiyuan (Frontiers in Language Sciences, 2025)
Focus is a core component of information structure that highlights the most prominent element in a sentence. While pitch and duration are well-established prosodic markers of focus in Mandarin Chinese, the role of word length has received less attention. Due to historical developments, many Mandarin words exhibit elastic length, appearing in both monosyllabic and disyllabic forms. In modern Chinese, however, there is a strong prosodic preference for disyllabic words as the minimal prosodic unit. This study tested whether using monosyllabic verbs in focus position disrupts reading fluency due to prosodic mismatch. Thirty-seven native Mandarin speakers read sentences silently while their eye movements were recorded. The study employed a 2 × 2 factorial design that crossed focus status (focus vs. no focus) with word length (monosyllabic vs. disyllabic). Linear mixed-effects models were used to analyze gaze duration, first fixation duration, first pass duration, regression path duration, regression count, fixation count, and skipping probability. The results show that monosyllabic verbs in focus positions attracted longer gaze durations, more fixations, and more regressions than disyllabic verbs, indicating a processing cost linked to prosodic mismatch. These findings reveal how prosodic and information-structural cues jointly guide real-time reading and confirm the processing advantage of disyllabic verbs in focus contexts.